Integrating Islamic Agenda in National Development Policy - A Malaysian Experience in Establishing A Waqf Corporation - Tan Sri Muhammad Ali Hashim (Sharia and Law Faculty, 2020)
The second critical challenge arises from a general apathy towards business among majority of Muslims, culminating in suspicion and distrust if not outright hostility towards business enterprise on the part of many, in spite of Islamâ€™s fundamental pro-business worldview. If allowed to prevail, such disdain towards business will only alienate the vast majority of especially young Muslims away from pursuing business careers which is the key to solving their persistent poverty problem. This negative attitude is partly the outcome of perception gaps regarding the role of business, especially among many influential Muslims who allege that business is harmful due to its â€œmaterialisticâ€ nature and â€œthis-worldlyâ€ tendencies. Such a perception may have arisen from observing Muslim entrepreneurs and businessmen conducting their business affairs in ways that are contrary to Islamic principles and teachings, often the result of their emulating and adopting un-Islamic business methods of global business. Needless to say, in todayâ€™s business-driven economic climate, a persistent anti-business outlook among Muslims will only worsen and prolong their state of economic powerlessness, exacerbating the ummahâ€™s economic marginalization and dependency on others. The bigger challenge facing the ummah today is therefore to find a creative, practical solution to successfully manage this paradox